The sustainability of emerging cane growers through youth involvement: a case study of the North Coast of KwaZulu-Natal in South Africa - Ntshangase, Wellington Mfanafuthi (University of the Free State, 2016)
𝑬𝒏𝒈𝒍𝒊𝒔𝒉 Agriculture is usually purported as one of the main solutions to the socio-economic problems besetting the rural areas. It is one of the main economic drivers in the rural areas of South Africa. The advantage of agriculture over other sectors is that it is labour-intensive and this is critical in a country such as South Africa that has a high level of unemployment. However, the main concern is that the current farmers are an ageing population and there seems to be reluctance on the part of the youth to follow agriculture as a career. There has also been a noticeable increase of youth migration to the cities in search of opportunities outside of agriculture. This study, which was conducted in the sugar industry, focused on the sustainability of cane production through youth involvement. The youth, aged between 14 and 35 years and whose parents are emerging cane growers (ECGs) were the main respondents in this study. In the follow-up focus group discussions the ECGs also participated. The ECG category refers to the cane growers who were previously disadvantaged (in the South African political and economic contexts) and includes small-scale growers and land-reform growers. According to SASA (the South African Sugar Association) there are approximately 22,500 registered sugarcane growers who annually produce on average 19 million tons of sugarcane in 14 mill-supply areas. This figure includes about 21,000 small-scale growers and 323 black emerging farmers. In the context of this study the term ECG refers to both SSGs (small-scale growers) and black emerging farmers (who are mainly referred to as LRGs – land reform growers – in the study). This study arose as a result of concerns regarding the relative lack of participation by young people in cane farming. This is not a study about youth in general but a specific study about young people whose parents or relatives are ECGs. There is a need to understand the seriousness of the challenges facing the sugar industry and strive to address them. One of these challenges is the drastic decline in cane production and there have been several efforts by the different role players aimed at remedying the situation. Millions of rands have been injected into the sugar industry to alleviate this problem. The researcher is of the view that these efforts will not lead to sustainable cane production if young people are not prepared to succeed their parents and become involved in cane farming. Contrary to popular beliefs relating to the youth’s negative perceptions and attitudes towards agriculture, the study found that young people whose parents are ECGs are prepared to succeed their parents as farmers. It showed that the youth are already involved in farming operations. They, however, would like to have their own farms instead of waiting for an inheritance. It also found a high level of involvement amongst these young people. The expected income was the main motivator for the young people to choose agriculture over other careers. The study’s recommendations focused on the need to ensure that the youth are able to own or lease land, on promotion of agriculture to youth from an early age, on access to funding for youth agripreneurs, and on providing support related to education and training for those choosing agriculture. ___________________________________________________________________

𝑨𝒇𝒓𝒊𝒌𝒂𝒂𝒏𝒔 Die bydrae van die landbou word algemeen beskou as potensieel een van die belangrikste faktore in die oplossing van die sosio-ekonomiese probleme wat die landelike gebiede teister, aangesien dit een van die vernaamste dryfkragte in die ekonomie van sodanige gebiede in Suid-Afrika uitmaak. Die voordeel wat die landbou bo ander sektore geniet, is dat dit arbeidintensief is, iets wat van kernbelang is in ’n land soos Suid-Afrika met sy uitermate hoë werkloosheidsyfer. Die grootste bekommernis is egter dat die huidige landbouers al ouer raak, terwyl daar onder die jeug blykbaar ’n onwilligheid heers om die landbou as beroep te kies. Verder is daar die afgelope tyd ook ’n merkbare toename in die aantal jeugdiges wat van die plase af stad toe migreer op soek na werksgeleenthede buite die landbou. Hierdie navorsingsprojek is in die suikerbedryf uitgevoer en spits hom toe op die volhoubaarheid van suikerrietverbouing deur die jeug daarby te betrek. Die meeste respondente in hierdie projek was jeugdiges tussen die ouderdomme van 14 en 35 jaar wie se ouers ontluikende suikerboere (ECG’s) is. Die ECG’s het ook self aan die opvolg-fokusgroepbesprekings deelgeneem. Die benaming ECG verwys na suikerrietkwekers wat voorheen (gesien binne die Suid-Afrikaanse politieke en ekonomiese verband) benadeel is. Dit sluit in dié wat op klein skaal boer asook dié wat a.g.v. grondhervorming tans opkomende landbouers is. Volgens SASA (die Suid-Afrikaanse Suikervereniging) tel daar huidiglik sowat 22,500 as geregistreerde suikerrietboere, wat jaarliks gesamentlik gemiddeld 19 miljoen ton suikerriet in 14 suikermeulgebiede lewer. Dié syfer sluit in sowat 21,000 kleinboere en 323 ontluikende swart boere. In hierdie verhandeling verwys die term ECG na sowel SSG’s (klein-skaal-boere) as swart ontluikende boere (na wie hoofsaaklik as LRG’s – grondhervormingskwekers – verwys word.) Hierdie projek het sy ontstaan te danke aan kommer oor jong mense se betreklike gebrek aan deelname aan suikerrietverbouing. Die projek gaan nie oor die jeug oor die algemeen nie: dit spits hom spesifiek toe op jong mense wie se ouers of familie ECG’s is. Dit is noodsaaklik dat die erns van die uitdagings wat die suikerbedryf in die gesig staar, begryp word, ten einde dit die hoof te bied. Een sodanige uitdaging is die snelle afname in die lewering van suikerriet. ’n Aantal pogings is al deur verskeie rolspelers aangewend om die toestand aan te spreek. Miljoene rand is reeds in die suikerbedryf ingespuit om die probleem te probeer oplos. Die navorser is van mening dat sodanige optrede nie tot volhoubare suikerrietlewering sal lei nie tensy jong mense bereid is om hul ouers op te volg en self aan suikerrietverbouing deel te neem. Teenstrydig met die algemeen aanvaarde oortuiging dat die jeug ’n negatiewe houding en opvatting teenoor die landbou koester, is bevind dat jong mense wie se ouers ECG’s is, self bereidwillig is om hul ouers as landbouers op te volg. Daar is bewys dat jeugdiges alreeds betrokke is by boerbedrywighede. Hulle verkies egter om ’n eie plaas te besit in plaas daarvan dat hulle wag om ’n familieplaas te erf. Daar is ook bewys dat sodanige jong mense reeds diep betrokke is by landboubedrywighede. Die verwagte lone was die belangrikste beweegrede wat hulle genoop het om die landbou bo ander loopbane te verkies. Die aanbevelings van die navorsing is toegespits op die noodsaaklikheid dat die jeug in staat gestel moet word om self grond te besit of te huur, dat hulle van ‘n vroeë ouderdom aangemoedig moet word om die landbou as beroep te kies, dat bevondsing bekom moet word ten behoewe van jong agripreneurs en dat bystand ten opsigte van onderrig en opleiding voorsien moet word aan diegene wat die landbou as beroep kies. ___________________________________________________________________

𝑺𝒆𝑺𝒐𝒕𝒉𝒐 Temo jwalo ka kamehla e hlahella e le e nngwe ya ditharollo tsa nnete ho mathata a setjhaba a moruo a tobileng dibaka tse ka ntle ho ditoropo. Temo ke mokgwa o mong wa pele wa ho nyolla moruo dibakeng tse ka ntle ho ditoropo Afrika Borwa. Molemo wa temo ke hore e hloka basebetsi ba bangata mme sena se bohlokwa haholo naheng ya Afrika Borwa e nang le batho ba bangata ba hlokang mosebetsi. Leha ho le jwalo, taba e hwayahwayang ke hore dihwai tse teng ha jwale ke batho ba seng ba hodile haholo mme ho bonahala batjha ba na le lesisitheo ho ithutela lefapha la temo. Hape ho bonahala sekgahla sa batjha ba fallelang ditoropong ho ya batla mekgwa ya ho phela ka ntle ho temo. Boithuto bona bo entswe femeng ya tswekere, bo tsepamisitse maikutlo ho tlhahiso ya mmoba ka batjha. Batjha ba dilemong tse pakeng tsa leshome le metso e mene le tse mashome a mararo a metso e mehlano le batswadi ba bona, ba bile le seabo diphuputsong tsena. Batjha bana ke bona ba bopileng sehlopha se kgethehileng sa diphuputso. ECG ke sehlopha sa dihwai tsa mmoba tseo e sa leng di sekisetswa (Ditabeng tsa Dipolotiki Afrika Borwa) ba kenyeletsa dihwai tse lemang hanyenyane le ba kabobotjha ya lefatshe. Ho ya ka mokgatlo wa SASA (South African Sugar Association), ho na le dihwai tsa tswekere tse 22, 500 tse ingodisitseng ho bahlahisi ba selemo ba hlahisang ditone tse dimilone di 19 tsa tswekere ka 14 phepelo ya dibaka ka dijo. Dipalopalo tsena di kenyeletsa bahlahisi ba banyenyane le dihwai tsa batho ba batsho ba 323 tseo e leng hona di qalang. Maemong a diphuputso tsena, ECG e bolela di-SSG (ba hlahisang hanyenyane) le bahlahisi ba batho ba batsho bao e leng hona ba qalang (ba tsebahalang ka hore ke LRG-land Reform Growers) diphuputsong tsena. Diphuputso tsena di qholoditswe ke dingongoreho mabapi le tlhokeho ya batjha ba bang le seabo temong ya tswekere. Diphuputso tsena ha di tadimane le batjha bohle empa di batla ho utlwisisa botebo ba diqholotso tse tobaneng le temo ya tswekere le ho fihlela mawala a mmalwa a ka thusang ho tsitsisa temo ya mmoba. E nngwe ya diqholotso tsena ke ho theoha ka sekgahla hwa tlhahiso ya tswekere mme ho bile le mawala a mangata a entsweng ke ba nang le kobo ya bohadi ba mmalwa ba rerileng ho tlisa tharollo bothateng bona. Dimiliyone tsa diranta di fanwe ho rarolla bothata bona tlhahisong ya tswekere. Mofuputsi o na le maikutlo a hore mawala ana ha a na ho tlisa tharollo ya moshwelella tlhahisong ya tswekere ha feela batjha ba sa ikemisetsa ho latela batswadi ba bona mme ba ba sehlahlo ditabeng tsa ho hlahisa mmoba. Kgahlanong le ditumelo tse tsebahang ka hohle ka hore batjha ha ba rate ebile ba na le lenyatso ditabeng tsa temo, diphuputso tsena di sibolotse hore batjha bao batswadi ba bona e leng di-ECG ba ikemiseditse ho latela batswadi ba bona ka bohwai. Diphuputso tsena di bontsha batjha ba ikemiseditse ho kenella mesebetsing ya temo. Leha ho le jwalo ba ka rata ho ba le dipolasi tseo eleng tsa bona ho na le ho emela ho ba majalefa. Ho fumanehile hore batjha ba bangata ba bile le seabo. Tjhelete e lebeletsweng ke yona e nyollang meya ya batjha ho kgetha temo ha ba ya dithutong tsa boemo bo hodimo. Dikgothaletso tsa diphuputso tsena di tsepame hodima hore batjha ba nnetefaletswe hore ba tla fuwa mangolo a kabo ya mobu, ho nyolla temo ka batjha, hore batjha ba fumane tshehetso ya bohwebi ya dihwai le hore ba fumane tshehetso ya Thuto le Kwetliso ho ba kgethang temo. ___________________________________________________________________

𝑰𝒔𝒊𝒁𝒖𝒍𝒖 Ezolimo zivame ukuthathwa njengesinye sezixazululo ezinkingeni zenhlalo nomnotho ezikhungethe izindawo zasemakhaya. Ingenye yezinto ezihamba phambili kwezomnotho ezindaweni zasemakhaya eNingizimu Afrikha. Okuhle ngezolimo kunezinye izinhlaka ukuthi zidinga abasebenzi abaningi futhi lokhu kubalulekile ezweni elifana neNingizimu Afrikha elinezinga eliphezulu labantu abangasebenzi. Nokho okukhathaza kakhulu wukuthi abalimi bamanje bangabantu asebekhulile futhi kubonakala kunokungabaza kubantu abasha ekutheni bafundele umkhakha wezolimo. Kuphinde kwaba nokwanda okuphawulekayo kokufudukela kwentsha emadolobheni iyofuna amathuba ngaphandle komkhakha wezolimo. Lolu cwaningo olwenziwa embonini kashukela, lugxile ekugcineni ukukhiqizwa komoba ngokubandakanya intsha kule mboni. Intsha eneminyaka ephakathi kweyi-14 kuya kwengama-35 futhi abazali bayo abangabalimi bomoba abasafufusa yibona ababe ngababambiqhaza abakhulu kulolu cwaningo. Ezingxoxweni ezilandelayo zeqoqo elicwaningwayo abalimi bomoba abasafufusa nabo babambe iqhaza. Umkhakha wabalimi bomoba abasafufusa ubhekise kubalimi bomoba ababencishwe amathuba phambilini (ezimweni zezombusazwe nezomnotho eNingizimu Afrikha) futhi uhlanganisa abalimi abancane nabatshali bezinguquko zomhlaba. NgokweSASA (South African Sugar Association) balinganiselwa ezi-22 500 abalimi bomoba ababhalisiwe abakhiqiza cishe amathani ayizigidi eziyi-19 ngonyaka ezindaweni eziyi-14 okugaywa kuzo. Lesi sibalo sibandakanya abalimi abasafufusa ababalelwa ezi-21 000 kanye nabalimi abamnyama abasafufusa abangama-323. Ngokwalolu cwaningo igama elithi abalimi bomoba abasafufusa libhekisela kukho kokubili abalimi abancane kanye nabalimi abamnyama abasafufusa ababizwa kakhulu ngokuthi abalimi bezinguquko zomhlaba ocwaningweni. Lolu cwaningo luqhamuke ngenxa yokukhathazeka mayelana nokungahlanganyeli kwabantu abasha ekulimeni umoba. Lolu akulona ucwaningo olumayelana nentsha jikelele kodwa ucwaningo olumayelana nentsha enabazali noma izihlobo zayo ezingabalimi bomoba abasafufusa. Kunesidingo sokuqonda ubucayi bezinselelo ezibhekene nemboni kashukela futhi silwele ukubhekana nazo. Enye yalezi zinselelo ukwehla okukhulu kokukhiqizwa kukamoba futhi kube nemizamo eminingana yababambe iqhaza abahlukene okuhloswe ngayo ukulungisa lesi simo. Sekufakwe izigidi zamarandi embonini kashukela ukuze kudambiswe le nkinga. Umcwaningi unombono wokuthi le mizamo ngeke iholele ekugcineni ukukhiqizwa komoba uma intsha ingazimisele ukungena ezinyathelweni zabazali bayo futhi ibambe iqhaza ekulimeni umoba. Ngokuphambene nezinkolelo ezivamile eziphathelene nemibono yentsha engemihle ngezolimo, ucwaningo lwathola ukuthi abantu abasha abanabazali abangabalimi bomoba abasafufusa bazimisele ukuhamba ezinyathelweni zabazali babo zokuba abalimi. Lukhombise ukuthi intsha isivele ibambe iqhaza ekulimeni. Nokho, bangathanda ukuba namapulazi abo esikhundleni sokulinda ifa. Iphinde yathola izinga eliphezulu lokuzibandakanya kwalabantu abasha. Imali ebilindelwe yiyona eyagqugquzela intsha ukuthi ikhethe ezolimo kuneminye imikhakha. Izincomo zocwaningo zazigxile esidingweni sokuqinisekisa ukuthi intsha iyakwazi ukuba nomhlaba okungowayo noma ukuqasha umhlaba, ekukhuthazeni ezolimo entsheni kusukela isencane, ekutholeni uxhaso lwezimali zentsha yezolimo, kanye nokuhlinzeka ngoxhaso oluhlobene nemfundo nokuqeqeshwa kwalabo abakhetha ezolimo. ___________________________________________________________________
Thesis (Ph.D.(Sustainable Agriculture))--University of the Free State, 2016
Keywords: Succession; Involvement; Participation; Youth; Perceptions; Attitudes; Cane grower; Land reform grower; Emerging cane grower; Small scale grower; Sustainability; Cane production; Sugarcane -- South Africa --KwaZulu-Natal